2019
DOI: 10.3389/fmicb.2018.03239
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of CTX-M-Producing Escherichia coli in Freshwater Fishes From a French Watershed (Burgundy)

Abstract: The burden of extended-spectrum β-lactamases producing Escherichia coli (ESBL-Ec), has increased over several decades. Freshwater ecosystems are suspected to play an important ecological and evolutionary role in driving the dissemination of antimicrobial resistance. The aim of our study was to decipher the occurrence of ESBL-Ec in a small watershed (Ouche river, Burgundy, France), targeting environmental matrices and fishes. Among cefotaxime resistant E. coli (ctxR Ec) isolates, we detected and characterized 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…ST131 UTI is associated with self-reported consumption of shrimp and contact with fish. A recent study isolated several clinically relevant ExPEC STs from fish, including ST10, ST38, and ST131, which suggests that an aquatic reservoir may exist for ExPEC STs [36]. Women with ST131 or ST69 UTI reported less frequent consumption of antibiotic-free meats.…”
Section: Discussionmentioning
confidence: 99%
“…ST131 UTI is associated with self-reported consumption of shrimp and contact with fish. A recent study isolated several clinically relevant ExPEC STs from fish, including ST10, ST38, and ST131, which suggests that an aquatic reservoir may exist for ExPEC STs [36]. Women with ST131 or ST69 UTI reported less frequent consumption of antibiotic-free meats.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven (11) strains of E. coli belonging to the pathovars Enteropathogenic E. coli (EPEC=4), Shiga toxinogenic E coli (STEC=5), Enteroinvasive E. coli (EIEC=2) from our previous work on gills (7) and viscera (4) of fish Oreochromis niloticus, was tested by Müller-Hinton agar diffusion method according to Antibiogram Committee of French Society of Microbiology [16]. According to EUCAST-CASFM recommendations on antibiotics used in case of infection with enterobacteria and in view of the multi-drug resistance observed in recent years, 19 antibiotics divided into 9 differents families (Penicillins, Cephalosporins, Monobactam, Carbapenems, Quinolone, Aminoside, Cyclin, Phenicol, Phosphonique Acid) were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial resistance is a real public health problem. They are found in humans [9]; animals [10,11]; and also in the environment [12]. Antibiotic-resistant bacteria of animal origin can be transmitted to humans through the ingestion of contaminated food, direct contact with animals or their environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bollache et al. (2018) reported that E. coli are producers of broad‐spectrum beta‐lactamases in several fish species. Therefore, E. coli isolates were excluded as a probiotic potential for A. gigas , although this species of Gammaproteobacteria has been used as a probiotic for other animal species by one century (Wassenaar, 2016).…”
Section: Figurementioning
confidence: 99%